Mesoporous Silica MCM-48 as Chloramphenicol Adsorbent - Taba, Paulina; Jannah, Miftahul; Hala, Yusafir (Indonesian Journal of Chemical Research, 2021)
This study is aimed to determine the potential use of MCM-48 to adsorb chloramphenicol pollution. Chloramphenicol adsorption was conducted at various times contact and concentration. Adsorption isotherm was studied by comparing Langmuir and Freundlich adsorption isotherm. The results showed that chloramphenicol adsorption was suited to Freundlich isotherm with an optimum contact time of 80 minutes